Not a happy family eaudiobook A novel. - Lapena, Shari (Penguin Audio, 2021)
AN INSTANT NEW YORK TIMES BESTSELLER! Another thrilling domestic suspense novel from the New York Times bestselling author of The Couple Next Door “Lapena is a master of manipulation. With her latest page-turning thriller… she is once again at the top of her game.” —USA Today “In this fast-paced, twisted family saga, Shari Lapena keeps you guessing until the very last page...” — Paula Hawkins In this family, everyone is keeping secrets—even the dead. Brecken Hill in upstate New York is an expensive place to live. You have to be rich to have a house there, and Fred and Sheila Merton certainly are rich. But even all their money can't protect them when a killer comes to call. The Mertons are brutally murdered after a fraught Easter dinner with their three adult kids. Who, of course, are devastated.   Or are they? They each stand to inherit millions. They were never a happy family, thanks to their vindictive father and neglectful mother, but perhaps one of the siblings is more disturbed than anyone knew. Did someone snap after that dreadful evening? Or did another person appear later that night with the worst of intentions? That must be what happened. After all, if one of the family were capable of something as gruesome as this, you'd know.   Wouldn't you?